2020
DOI: 10.1136/bmjgh-2020-003421
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in healthcare services during the COVID-19 pandemic in China

Abstract: IntroductionThe COVID-19 pandemic caused a healthcare crisis in China and continues to wreak havoc across the world. This paper evaluated COVID-19’s impact on national and regional healthcare service utilisation and expenditure in China.MethodsUsing a big data approach, we collected data from 300 million bank card transactions to measure individual healthcare expenditure and utilisation in mainland China. Since the outbreak coincided with the 2020 Chinese Spring Festival holiday, a difference-in-difference (DI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 20 publications
7
78
2
3
Order By: Relevance
“…Dental students and interns were excluded. The sample size was calculated [23] based on previous estimates: Zhang et al [24] reported that the percent change in healthcare services utilization post epidemic ranged from 12 to 18% around the mean hypothesized to be 50%. Thus, in a best-case scenario, participants may still follow the pre-pandemic estimates (50%) or their utilization may have dropped to a worst case scenario of 12%-18%.…”
Section: Participants and Sample Sizementioning
confidence: 99%
“…Dental students and interns were excluded. The sample size was calculated [23] based on previous estimates: Zhang et al [24] reported that the percent change in healthcare services utilization post epidemic ranged from 12 to 18% around the mean hypothesized to be 50%. Thus, in a best-case scenario, participants may still follow the pre-pandemic estimates (50%) or their utilization may have dropped to a worst case scenario of 12%-18%.…”
Section: Participants and Sample Sizementioning
confidence: 99%
“…Outpatient care, however, appears to have experienced a similar decline as urgent/emergent consults. Healthcare in general was lost during the height of the pandemic in various parts of the world [1,20,21]. It Whether loss of healthcare for non-COVID19 patients accounts for some proportion of excess mortality observed in different countries, including Spain, where excess mortality between February and May was 38% [22], is conceivable but difficult to assess.…”
Section: Plos Onementioning
confidence: 99%
“…Apart from its direct impact on infected patients, the SARS-CoV-2/COVID19 pandemic has had indirect collateral effects on patients with other pathologies not accessing standard of care for their diseases [1,2]. Surgery is one of the most resource-intensive areas of clinical medicine [3], and patients requiring surgical interventions have been particularly vulnerable in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…A prospective observational study from Nepal reported facility-based deliveries reduced by 51.4 %, with a corresponding increase in maternal and infant mortality(11). A nationwide study in China found that total healthcare expenditure and utilisation declined by 37.8% and 40.8%, respectively during the worst phase of the outbreak(12). The impact of the pandemic on surgical services is indicated in an expert elicitation exercise involving 190 countries.…”
Section: Introductionmentioning
confidence: 99%